EQUALITY OF LEGAL PROTECTION FOR CHILDREN VIS-À-VIS THE LAW IN CASES OF SEXUAL INTERCOURSE AND ABUSE IN THE PERSPECTIVE OF CHILD PROTECTION LAW - Andry Suharto; Tuti Widyaningrum (Cerdika: Jurnal Ilmiah Indonesia, 2024)
Child rape is a devastating form of sexual violence. This study aims to investigate and analyze the equality of legal protection for children in cases of sexual relations and abuse, focusing on the perspective of child protection law. This study uses methods that research normative juridical law. The results showed that the established legal law has partially worked for victims of child violence. The study's conclusions address whether the diversion process undertaken by law enforcement authorities in the Juvenile Justice System for adolescents facing legal problems due to allegations of sexual intercourse and/or maltreatment reflects gender non-discrimination.